Strategy for SME Business Development at the SME Catering Academy Center in Bandung - Wandi Kurniadi (International Journal of Economics and Management Research, 2022)
This study aims to formulate a SME business development strategy at the SME Catering Academy Center in Bandung City. The research was conducted with a descriptive-qualitative approach. Analysis techniques using internal-external situation analysis, merging using the IE matrix, and formulating strategies using SWOT A series of situational analyses of the business environment and incorporation using the IE matrix led to the understanding that Bandung City's SME Catering Academy is in the 2nd quadrant of the IE matrix, with recommendations for a general hold and maintenance strategy. While the SWOT analysis yielded several more specific strategic recommendations, namely improving corporate image in the eyes of consumers, strengthening digital capabilities, strengthening existing networks and adding new networks with various parties, increasing working capital for operational financing, expanding distribution, improving the quality of company human resources and employee development, expanding existing markets, carrying out production planning, and improving cost efficiency.